Quizziz: A Game-based Formative Assessment Tool for Enhancing Students Self-Regulated Learning - Capuno, Jenny Grace C. (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The primary purpose of this study is to determine whether Quizizz as a formative assessment tool enhances self-regulated learning among grade eight (8) Science learners of Sta. Catalina National High School, Candelaria, Quezon Province, Philippines. The study utilizes a mixed-methods research design to investigate whether Quizizz has the intended effect on the study samples. The study employs purposive sampling to identify the participants of the study. The experimental group (n=24) used Quizizz as an intervention before taking the formative test, while the control group (n=24) was not. The results reveal that the learners from the experimental group perform better than those from the control group. The findings suggest that using Quizizz improves learners' test scores resulting from self-regulated learning. The researcher identifies the grade 8 participants based on their capabilities to access the Quizizz platform.